A call for reducing tourism risk to environmental hazards in the Himalaya. (1st January 2023) - Ziegler, A. D.; Wasson, R. J.; Sundriyal, Y.; Srivastava, P.; Sasges, G.; Ramchunder, S. J.; Ong, C. E.; Nepal, S. K.; McAdoo, B. G.; Gillen, J.; Bishwokarma, D.; Bhardwaj, A.; et al.
ABSTRACT: As mountain tourism rapidly expands in remote landscapes, there is a critical need for improved disaster risk management to ensure the safety of tourists and industry workers, safeguard infrastructure designed to support tourism and service industries (e.g., transportation), as well as protect the local economies that have come to depend on tourism revenue. Drawing from recent disasters in the Himalaya, we present evidence that the promotion of safe and sustainable tourism is out of sync with the proliferation of inbound tourists who are prone to many types of environmental hazards. The key driver of this situation is commercialisation. Other factors include increased mobilities/access of tourists who are often unaware of or ill-prepared to cope with hazards; lack of regulations with respect to overcrowding, safety and building codes increased exposure to climate change phenomena; and limited disaster response capabilities, including responsibility at the local level. In this perspective we argue that this particularly complex situation is best addressed through the lens of a dynamic system, whereby strong leadership, increased regulation of access and participation, and enhanced professionalism via training are key leverage points in countering uncontrolled commercialisation that drives increased risk to known hazards. The inclusion of tourism into disaster risk management systems is also needed where hazard risks and tourist traffic are high, as tourists are part of the transient population who are often unfamiliar with local conditions and ill-prepared to cope with extreme adversity.